The effect of ferulic acid against cisplatin-induced ototoxicit - Fazile Nur Ekinci Akdemir; Mustafa Sitki Gozeler; Serkan Yildirim; Seda Askin; Muhammet Bahaeddin Dortbudak; Ahmet Kiziltunc (Medicine Science, 2018)
Ototoxicity refers to cellular damage or functional disorder developing in the inner ear in association with any therapeutic agent or chemical substance. Cisplatin, one of these agents capable of causing ototoxicity, is a chemotherapeutic used in several malignancies. Ferulic acid (FA) is a phenolic acid with known anti-oxidative and anti-inflammatory properties. The purpose of this study was to perform a biochemical and histopathological investigation of the protective efficacy of FA against cisplatin-induced ototoxicity in rats. Twenty-four Wistar rats were used in this study. Animals were randomly assigned into four groups of six rats each. Rats in the control group received intraperitoneal injection of 1 ml salin for four consecutive days. Rats in the cisplatin group received a single intraperitoneal administration of 10 mg/kg cisplatin. Rats in the FA group received intraperitoneal FA at 100 mg/kg for four days, and rats in the cisplatin+FA group received intraperitoneal FA at 100 mg/kg 1 h after administration of intraperitoneal cisplatin at 10 mg/kg, this procedure being performed for four consecutive days. Rats were sacrificed 24 h after the final drug administration. Cochlear tissues were removed for biochemical and histopathological analysis. MDA levels were significantly higher in cochlear tissues of the rats receiving cisplatin compared to the control group. MDA levels in rats receiving cisplatin and treated with FA were significantly lower than those in the cisplatin group. Activities of SOD and GPx decreased significantly in the cochleas of rats administered cisplatin compared to the control group. Both SOD and GPx activities were significantly higher in rats administered FA and cisplatin in combination compared to the cisplatin only. Histopathological evaluation of cochleas of the rats revealed significant protection of FA against cisplatin induced ototoxicity. This study, the first in the literature, shows that FA exhibits a protective effect against cisplatin-induced ototoxicity. [Med-Science 2018; 7(3.000): 528-31]